Legal Protection for Buyers in a Junk Sale and Purchase Agreement: Perlindungan Hukum Bagi Pembeli Dalam Perjanjian Jual Beli Barang Rongsokan - Afrizal, Afrizal; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to find out and examine the legal protection for buyers of junk goods, which focuses on the validity of the sale and purchase agreement of junk goods, as well as forms of preventive legal protection that can be carried out by junk collectors who are accused of being collectors. or the general public can defend themselves when they accidentally receive the proceeds of crime. This study uses a normative juridical method, with a statutory approach. The data comes from two main sources, namely the legal code and the criminal law code as primary legal materials and journals, books, doctrines as secondary legal materials. Using deductive analysis method. The conclusion of this study is that the sale and purchase agreement for junk goods is valid, when there is no violation of Article 1320 and Article 1457 of the Civil Code. As well as preventive legal protection efforts when accused of being a collector, such as a statement that the goods are junk from legal matters, transactions are carried out during the day, prices are according to the market and so on.